Alternative editing of cytochrome c oxidase III mRNA in trypanosome mitochondria generates protein diversity - Ochsenreiter, Torsten (2006)
Trypanosomes use RNA editing to produce most functional mitochondrial messenger RNA. Precise insertion and deletion of hundreds of uridines is necessary to make full-length cytochrome c oxidase III (COXIII) mRNA. We show that COXIII mRNA can be alternatively edited by a mechanism using an alternative guide RNA to make a stable mRNA. This alternatively edited mRNA is translated to produce a unique protein that fractionates with mitochondrial membranes and colocalizes with mitochondrial proteins in situ. Alternative RNA editing represents a previously unknown mechanism generating protein diversity and, as such, represents an important function for RNA editing.